Lion of Jordan : The Life of King Hussein in War and Peace - Shlaim, Avi (New York Alfred A. Knopf, 2008)
From the Publisher: During his long reign (1953-1999), King Hussein of Jordan was one of the most dominant figures in Middle Eastern politics and a consistent proponent of peace with Israel. This is the first major account of his life, written with access to his official documents and with the cooperation (but not approval) of his family and staff, and also extensive interviews with international policy makers. For more than forty years, Hussein walked a tightrope between the Palestinians and Arab radicals on the one hand and Israel on the other. Avi Shlaim reveals that, for the sake of dynastic and national survival, Hussein initiated a secret dialogue with Israel in 1963 that encompassed more than one thousand hours with Golda Meir, Shimon Peres, Yitzhak Shamir, Yitzhak Rabin, and countless others. Shlaim reconstructs this dialogue across battle lines from previously untapped Israeli records and the firsthand accounts of key participants, and makes clear that it was Israeli intransigence that was largely responsible for the failure to achieve a peaceful settlement between 1967 and 1994. At Hussein's memorial service at St. Paul's Cathedral, the Prince of Wales hailed him as "a man amongst men, a king amongst kings." Lion of Jordan illuminates the triumphs and disappointments, the qualities and character of this extraordinary soldier and statesman, and significantly rewrites the history of the Middle East over the past fifty years.
Include Index, Bibliography, Maps and Illustration
Keywords: Hussein, King of Jordan, 1935-1999 -- Jordan -- Politics and government